2023
DOI: 10.3390/su152316393
|View full text |Cite
|
Sign up to set email alerts
|

Does the Seat Matter? The Influence of Seating Factors and Motivational Factors on Situational Engagement and Satisfaction in the Smart Classroom

Guoqing Lu,
Qingtang Liu,
Kui Xie
et al.

Abstract: As a technology-enhanced student-centered learning environment, smart classrooms are becoming increasingly popular in higher education. It is undoubtedly important to understand how seating and motivational factors affect situational engagement and satisfaction in smart classrooms. Pre-survey, experience sampling method, and post-survey were used in this study to conduct a longitudinal survey of 113 pre-service teachers in three courses at a university in central China. Descriptive statistics, bivariate correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…Few studies have examined the correlation between sitting and learning. The seating factor predicted student situational engagement in a smart classroom [29]. The findings of this study are that each combination of depth and backrest height had different effects during each task, and sitting on the front one third of a chair with a lower backrest positively affected the performance of short, high-concentration learning tasks; the results suggest that schools and educational institutions should require students to temporarily maintain this seating condition and a lower backrest for short, high-concentration learning tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the correlation between sitting and learning. The seating factor predicted student situational engagement in a smart classroom [29]. The findings of this study are that each combination of depth and backrest height had different effects during each task, and sitting on the front one third of a chair with a lower backrest positively affected the performance of short, high-concentration learning tasks; the results suggest that schools and educational institutions should require students to temporarily maintain this seating condition and a lower backrest for short, high-concentration learning tasks.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, students are easily influenced by the students around them in the classroom learning process, and this implicit impact is often reflected in students' classroom learning statuses and academic performance. Lu et al [7] found that there was a significant effect from students' seating choices on classroom learning engagement. Putnik et al [8] found that there was also a significant correlation between student learning outcomes and social network structure characteristics.…”
Section: Introductionmentioning
confidence: 99%